Keefektifan Layanan Penguasaan Konten Tentang Mind Mapping untuk Meningkatkan Kemandirian Belajar - hidayah, arini; Setyowani, Ninik (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This study aims to: (1) determine the independence of student learning in class VIII of SMP Negeri 11 Pekalongan before being given service mastery of mind mapping content, (2) determine the independence of student learning in class VIII of SMP Negeri 11 Pekalongan after being given service mastery of mind mapping content, (3) determine differences the independence of student learning in class VIII of SMP Negeri 11 Pekalongan before and after services mastery of mind mapping content. This was an experimental study with the study design one group pre-test and post-test. The population in of  this study were are all of the students of class VIII of SMP Negeri 11 Pekalongan. The sampling technique that used is purposive sampling techniques. The method of collecting data in this study is using psychological scale in the form of independence of learninng  scale. The results showed that students learning independence increased after treatment in the form of services given control of the content of the mind mapping. So we can conclude that the services mastery of mind mapping content effective to enhance the independence learning of class VIII SMP Negeri 11 Pekalongan.